2018
DOI: 10.1140/epjb/e2018-90301-8
|View full text |Cite
|
Sign up to set email alerts
|

Sum-rules of the response potential in the strongly-interacting limit of DFT

Abstract: The response part of the exchange-correlation potential of Kohn-Sham density functional theory plays a very important role, for example for the calculation of accurate band gaps and excitation energies. Here we analyze this part of the potential in the limit of infinite interaction in density functional theory, showing that in the one-dimensional case it satisfies a very simple sum rule.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…It is evident that, in order to correctly describe how this potential behaves around its maximum, we need to include also the knowledge of how the comotion function diverges, while this information is not needed in the case of the maximum of the SCE Hartree XC potential. Nonetheless, our modeled SCE response potential correctly integrates to exactly one as it should, fulfilling a recently derived sum-rule . Moreover, excluding for a moment the point f mod ( a r ) = ∞ from our model comotion function, we can evaluate the analytical behavior of the step structure of the modeled SCE response potential, v resp,mod SCE , that is, the difference from its left and right limits toward a R , getting which differs from the exact step height in the model by the factor .…”
Section: Analytical 1d Model For V Hxc Sce and V Resp Sce In The Diss...mentioning
confidence: 70%
“…It is evident that, in order to correctly describe how this potential behaves around its maximum, we need to include also the knowledge of how the comotion function diverges, while this information is not needed in the case of the maximum of the SCE Hartree XC potential. Nonetheless, our modeled SCE response potential correctly integrates to exactly one as it should, fulfilling a recently derived sum-rule . Moreover, excluding for a moment the point f mod ( a r ) = ∞ from our model comotion function, we can evaluate the analytical behavior of the step structure of the modeled SCE response potential, v resp,mod SCE , that is, the difference from its left and right limits toward a R , getting which differs from the exact step height in the model by the factor .…”
Section: Analytical 1d Model For V Hxc Sce and V Resp Sce In The Diss...mentioning
confidence: 70%
“…We first consider two types of simple exponential basis functions (13) in the HL model, with exponents corresponding to the ionization energies obtained with our model Hamiltonian. So in the equations for x ± peak (16) and v kin (x ± peak ) (17), which are for exponential basis functions, we use the two values for a = 2 √ 2 I A with I A = − A according to cases 1 and 2 above, and the corresponding two values for b. This yields HL estimates for both the values at and the locations of the maxima, see option 1 and option 2 for exponential basis functions in Tab.…”
Section: B Numerical Resultsmentioning
confidence: 99%
“…This feature has received further interest in the literature. [11][12][13][14][15][16][17][18][19] In Ref. 4, it was demonstrated that such step structure (with height ∆I = I A − I B if A has higher ionization potential) is due to the response potential v resp .…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, our modelled SCE response potential correctly integrates to exactly one as it should, fulfilling a recently derived sum-rule. 62 Moreover, excluding for a moment the point f mod (a r ) = ∞ from our model co-motion function, we can evaluate the analytical behaviour of the step structure of the modelled SCE response potential, v SCE resp,mod , i.e. the difference from its left and right limits towards a R , getting…”
Section: Response Potential From the Coupling-constant Integrationmentioning
confidence: 99%